Paediatric multiple sclerosis: a case report of missed and dismissed diagnosis - saadi, nebal wael; Fahad, Qusay Abed (Journal of the Faculty of Medicine Baghdad, 2021)
Multiple Sclerosis (MS) is a chronic inflammatory autoimmune disease of the central nervous system (CNS). Up to 10 % of MS patients have onset in paediatric age group. Although the clinical profile of MS appears similar to that seen in adults, several features may differ and specific issues arise in children. Here, we reported a 12-year old girl who presented with 3-year history of episodes of seizures and facial nerve palsy and finally fatigue and cognitive impairment were noted and interfered with her academic performance. Because of the presumed atypical clinical presentations, the diagnosis was missed then dismissed despite neuroimaging features and CSF immunological findings that were highly suggestive of MS. Later, evolution of the disease by neuroimaging helped confirming the diagnosis and directed toward the delayed therapy.